First finding of Trypanosoma cruzi II in vampire bats from a district free of domestic vector-borne transmission in Northeastern Argentina - Argibay, Hernán D (2016)
Fil: Argibay, Hernán D. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Ecología,Genética y Evolución. Laboratorio de Eco-Epidemiología; Argentina.